ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI DI KECAMATAN PATAMPANUA KABUPATEN PINRANG - Sulaeman, Ardi (Cateris Paribus Journal, 2021)
This research aims to analyze the factors that affect the income of peanut farming in Bacukiki West District of Parepare City. It is hoped that this research can provide benefits to the authors and academics as scientific study materials and hopefully the results of the research become information for farmers of Peanuts in the West District of Parepare City Collection techniques used by observation, documentation and questionnaires. The data analysis technique in this study uses multiple linear regression analysis, this analysis is used to determine the factors that affect the income of farmers is the analysis of multiple regressions mathematically. The results showed that the widespread factors of land, labor, seed count, amount of fertilizer and the amount of pesticides simultaneously or together had a significant effect on the income of bean farmers in bacukiki district west of Parepare city but partially or individually only labor variables had a significant effect.